2020
DOI: 10.1111/jpm.12723
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of workplace violence and the psychological consequences of it among nurses working in psychiatric outpatient settings

Abstract: Accessible summary What is known on the subject? There is a scarcity of studies concerning violence in psychiatric outpatient settings in the 2010s in spite of the deinstitutionalization of psychiatric services. Previous research on violence in psychiatric outpatient settings has failed to consider the association between the psychological consequences of violence, exposures to violence and background factors. What the paper adds to existing knowledge? It has been known for some time that exposures to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Therefore, in order to prevent WPV, hospitals need to secure a sufficient number of nurses per patient and implement a WPV prevention and response program. In particular, nurses working in emergency and psychiatric departments have more experiences of violence (Copeland & Henry, 2018; Konttila et al., 2021). Therefore, it is necessary to conduct effective risk assessments in consideration of the department, and appropriate staffing and training are needed to help nurses cope with violence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to prevent WPV, hospitals need to secure a sufficient number of nurses per patient and implement a WPV prevention and response program. In particular, nurses working in emergency and psychiatric departments have more experiences of violence (Copeland & Henry, 2018; Konttila et al., 2021). Therefore, it is necessary to conduct effective risk assessments in consideration of the department, and appropriate staffing and training are needed to help nurses cope with violence.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural changes in nurses' view of aggression will lead to fewer conflicts between staff and patients, which, in turn, will lead to fewer patients being restrained (Tomagová et al, 2016). This is supported by researchers in other countries, who have concluded that there is a need for training programmes in order to change staff attitudes (Al-Awawdeh et al, 2016;James et al, 2011;Konttila et al, 2020;Tomagová et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Violence in the workplace increases the risk of severe stress among employees. In addition, workplace violence has been associated with a lack of quality sleep, depression, fatigue, insomnia, and post-traumatic stress disorder among employees [Andersen et al 2021;Lanctôt and Guay 2014;Konttila et al 2021]. Exposure to violence should never be accepted as part of any job [NIOSH 1996[NIOSH , 2004].…”
Section: Health Effects Of Workplace Violencementioning
confidence: 99%